Ablution spaces cleanliness : literature debate on the Malaysian mosque’s design - Hayder Jawad Shakir Haraty; Mohammad Yazah Mat Raschid; Nangkula Utaberta (Penerbit Universiti Kebangsaan Malaysia, 2019)
Mosques, as a place for Muslim prayers and other social activities to be performed, are built to worship the Almighty Allah at all times, aside from providing an environment that responses to the needs of devotees, as well as educating the future generation by the Quranic verses and the Prophet’s teachings. Deriving from the Holy Quran and the Prophet, purity is compulsory at all times for Muslims, and it has many denotations that are applicable during prayers and during the day. Muslims are required to pray five times a day, in which ablution has to be performed prior to praying. The ablution room is always integrated in all mosques designs as it is an unseparated element. As such, this paper looks into the hygienic consideration of the ablution space; it discusses prior statements and some Islamic perceptions pertaining to the design of the ablution space, as well as the cleanliness of space and person. Several researches have been analyzed to seek better understanding regarding the relationship between space cleanliness and Muslims in the design of mosques. The results from the discussion reveal that purity is required for internal and external cleanliness, in which the facilities of ablution space in mosques have to be specific so as to avoid any type of intervention for other various usages. The paper is an effort to generate better hygiene space in future designs of mosques with focus on the ablution space, as well as to respond to the Islamic teaching for ablution and purity.